Madness and Method: a Pastoral Theological Reflection - LaMothe, Ryan (Pastoral psychology, 2016)
This article is a reflection on pastoral method in light of the metaphor of madness. I consider the notion of madness in terms of how it is represented in Western thought and take these representations as prisms to reflect on the attributes of pastoral methodology. More specifically, I use the notions of unreason, otherness, creativity, rage, and folly to think about the strengths of pastoral method.